PENGISIAN JABATAN SEKRETARIS DESA DI KABUPATEN BANYUMAS (Studi Tentang Kebijakan Pengisian Jabatan Sekretaris Desa) - Hartini, Sri; Nassihudin, Abdul Aziz (Jurnal Dinamika Hukum, 2008)
Village secretary assumed as a strategic occupation in the village government because the function as a proxy lead village. At the moment, Law No. 32 Year 2004 concerning Local Government have made arrangement  this occupation status, which initially village secretary is not a public servant and now because some reasons will fill by Public Servant. How the policy of admission filling of this occupation? In the case, the government should make regulation which can guarantee the orderliness and protect the society. Keyword: Village, village secretary and government policy